2014
DOI: 10.1063/1.4864182
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of the central atom on the ionic liquid behavior: Phosphonium vs ammonium cations

Abstract: Density relaxation and particle motion characteristics in a non-ionic deep eutectic solvent (acetamide + urea): Time-resolved fluorescence measurements and all-atom molecular dynamics simulations J. Chem. Phys. 142, 034505 (2015) The influence of the cation's central atom in the behavior of pairs of ammonium-and phosphoniumbased ionic liquids was investigated through the measurement of densities, viscosities, melting temperatures, activity coefficients at infinite dilution, refractive indices, and toxicity aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 136 publications
(92 citation statements)
references
References 37 publications
8
83
1
Order By: Relevance
“…This charge distribution also has a significant impact on other properties, such as in the phase diagrams of binary IL-water systems, densities and viscosities, as previously shown. 60,61 On the other hand, the C-H bonds of the alkyl groups in tetraalkylphosphonium ILs are hardly polarised compared to tetraalkylammonium, which is clearly shown by the low α-value of the former IL. This behaviour can be attributed to the different charge distribution/contribution of the ammonium-and phosphonium-based IL cations as previously demonstrated by Carvalho et al 60,61 The higher acidity afforded by ammonium-based ILs also correlates well with their lower ability to form two-aqueous phase systems reflected by a higher ability to hydrogenbond with water.…”
Section: Experimental Kamlet-taft Solvatochromic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…This charge distribution also has a significant impact on other properties, such as in the phase diagrams of binary IL-water systems, densities and viscosities, as previously shown. 60,61 On the other hand, the C-H bonds of the alkyl groups in tetraalkylphosphonium ILs are hardly polarised compared to tetraalkylammonium, which is clearly shown by the low α-value of the former IL. This behaviour can be attributed to the different charge distribution/contribution of the ammonium-and phosphonium-based IL cations as previously demonstrated by Carvalho et al 60,61 The higher acidity afforded by ammonium-based ILs also correlates well with their lower ability to form two-aqueous phase systems reflected by a higher ability to hydrogenbond with water.…”
Section: Experimental Kamlet-taft Solvatochromic Parametersmentioning
confidence: 99%
“…60,61 On the other hand, the C-H bonds of the alkyl groups in tetraalkylphosphonium ILs are hardly polarised compared to tetraalkylammonium, which is clearly shown by the low α-value of the former IL. This behaviour can be attributed to the different charge distribution/contribution of the ammonium-and phosphonium-based IL cations as previously demonstrated by Carvalho et al 60,61 The higher acidity afforded by ammonium-based ILs also correlates well with their lower ability to form two-aqueous phase systems reflected by a higher ability to hydrogenbond with water. 62 Two sets of imidazolium-based ILs were also studied: one with 1-methyl-3-alkylimidazolium-based asymmetric ILs and the other consisting of 1,3-dialkylimidazoliumbased symmetric ILs.…”
Section: Experimental Kamlet-taft Solvatochromic Parametersmentioning
confidence: 99%
“…16,17,20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Table S1 of the ESI. † While the other descriptors were obtained without the need of any geometry optimization process, the QTMS parameters were derived from the ab initio based optimized geometry at the HF/6-31G(d) level of theory, and were limited to only cations.…”
Section: The Dataset and Descriptorsmentioning
confidence: 99%
“…Usually, the increase in the alkyl chain length leads to a greater negative impact (Garcia et al, 2005;Latala et al, 2009a). Regarding the cation core, some studies report that aromatic cations (imidazolium and pyridinium) normally are more toxic than non-aromatic ILs, such as pyrrolidinium, piperidinium (Ventura et al, 2013), phosphonium and ammonium (Carvalho et al, 2014). Although sometimes neglected, the toxicity of anions such as trifluoromethanesulfonate, dicyanamide (Steudte et al, 2012), tetrafluoroborate (Pinto et al, 2012) and bis(trifluoromethanesulfonyl)imide (Costa et al, 2015) has been demonstrated.…”
Section: Introductionmentioning
confidence: 98%